Penerapan Etika Kepemimpinan Kepala Sekolah dalam Membangun Budaya Organisasi yang Positif Bagi Guru dan Staff di Sekolah (Studi Kasus di MTs Nurul Islam Yasni Sukabumi) - Suharyanto H. Soro; Ilman Shafhan Jamil; Ahmad Halian; Inayah Siti Nadiyah (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to analyze the application of ethical leadership by school principals as uswatun hasanah (a good role model) in building a positive organizational environment for teachers and staff. The research employs a descriptive qualitative approach by collecting data through in-depth interviews, observations, and documentation at MTs Nurul Islam Yasni Sukabumi, which serves as the subject of the study. The findings indicate that the school principal plays a strategic role in creating a conducive learning environment by exemplifying integrity, fairness, and empathy. The principal also practices the principles of deliberation and transparency in decision-making, involving the entire school community. Additionally, the principal successfully addresses globalization challenges, such as the influence of digital technology and cultural differences, through digital literacy, strengthening local values, and fostering collaboration with various stakeholders. The implementation of leadership based on uswatun hasanah has had a positive impact on teacher professionalism, student enthusiasm for learning, and harmony within the school community, thereby enhancing the overall quality of education. This study concludes that ethical value-based leadership by school principals is a key factor in addressing the dynamics of globalization in the field of education.